Morphological profiling of environmental chemical combinations - images, pipelines, and features - Rietdijk, Jonne; Aggarwal, Tanya; Georgiev, Polina; Lapins, Maris; Carreras-Puigvert, Jordi; Spjuth, Ola (Uppsala University, 2022)
Abstract:

Environmental chemicals are commonly studied one at a time, and there is a need to advance our understanding of the effect of exposure to their combinations. Here we apply high-content microscopy imaging of cells stained with multiplexed dyes (Cell Painting) to profile the effects of Cetyltrimethylammonium bromide (CTAB), Bisphenol A (BPA), and Dibutyltin dilaurate (DBTDL) exposure on four human cell lines; both individually and in all combinations. We show that morphological features can be used with multivariate data analysis to discern between exposures from individual compounds, concentrations, and combinations. CTAB and DBTDL induced concentration-dependent morphological changes across the four cell lines, and BPA exacerbated morphological effects when combined with CTAB and DBTDL. Combined exposure to CTAB and BPA induced changes on the ER, Golgi apparatus, nucleoli and cytoplasmic RNA in one of the cell lines. Different responses between cell lines indicate that multiple cell types are needed when assessing combination effects. The rapid and relatively low-cost experiments combined with high information content make Cell Painting an attractive methodology for future studies of combination effects. All data in the study is made publicly available on Figshare.

Description:

This dataset includes raw images, CellProfiler image analysis pipelines and extracted features of a morphological profiling study focussing on combination effects of environmental chemicals. Specifically, the study included U-2 OS, A549, Caco-2 and MCF7 cells exposed to three environmental chemicals (Hexadecyltrimethylammonium bromide, Bisphenol A, and Dibutyltin dilaurate) as single, duo and triple combinations, at three different doses (1uM, 6uM, 12uM), exposed for 24 hours. Cells are labelled with six labels that characterise eight cellular components and organelles (from the "Cell Painting" assay). This experiment consists of four 384-well plates, where each plate includes two cell lines. 6 fields of view per well are captured using an ImageXpress Micro XLS (Molecular Devices) microscope with a 20X objective. Each field was imaged in five channels (detection wavelengths), and each channel is stored as a separate, grayscale image file in TIFF format. The channel names (w1-w5) correspond to the following stains: w1 = Hoechst 33342 (HOECHST); w2= MitoTracker (MITO); w3= Wheat Germ Agglutinin/Alexa Fluor 555 + Phalloidin/Alexa Fluor 568 (PHAandWGA); w4= SYTO 14 green (SYTO);w5= Concanavalin A/Alexa Fluor 488 (CONC).

Organisation of files:

1) Raw image data:


- A549-1.tar.gz (replicate 1)

- A549-2.tar.gz (replicate 2)

- CACO2-1.tar.gz (replicate 1)

- CACO2-2.tar.gz (replicate 2)

- MCF7-1.tar.gz (replicate 1)

- MCF7-2.tar.gz (replicate 2)

- U2OS-1.tar.gz. (replicate 1)

- U2OS-2.tar.gz (replicate 2)



2) Image analysis pipelines (CellProfiler 4.0.7):

CellProfiler_Analysis_Pipelines.zip:


- QC.cppipe: Quality control pipeline

- ILLUM.cppipe: illumination correction pipeline

- FEATURES_A549: feature extraction pipeline A549

- FEATURES_Caco2: feature extraction pipeline Caco-2

- FEATURES_MCF7: feature extraction pipeline MCF7

- FEATURES_U-2OS: feature extraction pipeline U-2 OS



3) Extracted feature data:

Morphological_features.zip:


- Morphological_Features_A549

- Morphological_Features_Caco2

- Morphological_Features_MCF7

- Morphological_Features_U2OS



4) Metadata:

The file “metadata-file.csv“ contains the metadata in CSV format, with the following fields:


- cellLine: corresponds to cell line (A549, U-2 OS, Caco-2, MCF7)

- well_id: well allocation in the 96-well plate

- cmpd_1: name of compound

- cmpd_2: name of second compound

- cmpd_3: name of third compound

- cmpd_conc_uM: dose of compound(s)

- conc_units: concentration unit

- pert_type: poscon= phenotypic reference compounds, negcon= negative controls, trt=treatment, blank= no treatment

- treat_id: short code identifier per treatment



The file “compounds-file.csv“ contains detailed information about the chemicals in CSV format, with the following fields:


- cmpd_name: compound name

- cmpd_id: short code identifier for compound

- batch_nr: batch number for compound

- pubchemCID

- pert_type: poscon= phenotypic reference compounds, negcon= negative controls, trt=treatment, blank= no treatment

- morphChanges: expected morphological change

- InChIKey

- SMILES



The file "manifest-file.txt" contains a list of files and file sizes in this dataset.
Keywords: Environmental assessment and monitoring; Toxicology (incl. clinical toxicology); Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi